7 - An Empirical Analysis of Food Insecurity in Ethiopia: The Case of North Wello: 10.4314/ad.v27i1.22154 - Demeke, Assefa; Ramakrishna, G. (Africa Development, 2022)
In this paper an attempt is made to assess food insecurity situation in the North Wello zone of Ethiopia using household data. To this end, a food balance sheet and an aggregate household food security index have been constructed and food insecurity causation has been studied using a logit model. The survival mechanisms of the people also have been recorded. The evidence suggests that the study area is highly food insecure and survival mechanisms are traditional. Along with food availability and entidement, attitudinal variables also influence food insecurity.